Mobility and muscle strength trajectories in old age: the beneficial effect of Mediterranean diet in combination with physical activity and social support - Marguerita Saadeh; Federica Prinelli; Davide L. Vetrano; Weili Xu; Anna-Karin Welmer; Serhiy Dekhtyar; Laura Fratiglioni; Amaia Calderón-Larrañaga (BMC, 2021)
Abstract Introduction Decline in physical function varies substantially across older individuals due to several extrinsic modifiable factors such as dietary patterns, physical activity and social support. We aimed to determine the association of these factors and their interaction with mobility and muscle strength decline. Methods We analyzed data from 1686 functionally healthy individuals aged 60 + from the population-based Swedish National study on Aging and Care in Kungsholmen (SNAC-K). The Mediterranean Diet Score (MDS) was calculated based on a validated food frequency questionnaire. Self-reported physical activity was categorized based on current recommendations, and social support was measured according to participants' perceived material and psychological support from relatives and friends. Participants' physical function was assessed over 12 years through changes in walking speed (m/s) and chair stand time (s). Linear mixed models adjusted for socio-demographic and clinical factors were used. In order to explore the combined effect of the different exposures, two indicator variables were created by cross-classifying individuals' levels of Mediterranean diet adherence and social support or physical activity. Results Participants with a high adherence to Mediterranean diet were primarily < 78 years (82.3%), women (56.1%), married (61.1%), with university education (52.8%), high levels of social support (39.3%) and health-enhancing levels of physical activity (51.5%). A one-point increase in MDS (score range 0-9) was associated with less annual deterioration in walking speed (β*time[year] = 0.001; p = 0.024) and chair-stand time (β*time[year] = -0.014; p = 0.008). The potential protective effect of Mediterranean diet was highest among participants reporting high social support (β*time[year] = -0.065, p = 0.026 for chair stands) and high physical activity (β*time[year] = 0.010, p = 0.001 for walking speed), beyond the effect of each exposure individually. Conclusion A higher adherence to Mediterranean diet, especially in combination with recommended levels of physical activity and high social support, may contribute to delay the decline in physical function observed with aging.